2010
DOI: 10.1021/ma9025948
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalysis: Opportunities and Challenges for Polymer Synthesis

Abstract: Organocatalysis offers a number of opportunities in polymer synthesis and was among the earliest methods of catalyzing the synthesis of polyesters. In the following Perspective we attempt to highlight the opportunities and challenges in the use of organic molecules as catalysts or initiators for polymerization reactions. The ring-opening polymerization of cyclic monomers is used as a representative polymerization process to illustrate some of the features of organic catalysts and initiators and to compare them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
665
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 815 publications
(699 citation statements)
references
References 192 publications
15
665
1
Order By: Relevance
“…As for organocatalysts, the application of N-heterocyclic carbene (NHC) and its derivatives to ROP has attracted considerable attention. It can efficiently promote the polymerization of lactide and related monomers under mild conditions [23][24][25][26]. These organocatalysts often exhibit higher functional group tolerance [27] than metal-based complexes, and inherently work under milder conditions.…”
Section: Introductionmentioning
confidence: 99%
“…As for organocatalysts, the application of N-heterocyclic carbene (NHC) and its derivatives to ROP has attracted considerable attention. It can efficiently promote the polymerization of lactide and related monomers under mild conditions [23][24][25][26]. These organocatalysts often exhibit higher functional group tolerance [27] than metal-based complexes, and inherently work under milder conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[26] Organic catalysts such as thiourea/amine derivatives, are highly selective and lead to polymers of narrow polydispersity indices (PDIs). [26] Most often, studies on Ln III luminescent PC materials involve the doping of the PC materials with Eu III ions. [10,11,27] Rubira and co-workers [11] showed that Eu III sensitization can be achieved by doping a blend of PC/PMMA with a Eu III acetylacetonate complex.…”
Section: Introductionmentioning
confidence: 99%
“…17 As an organo-based catalyst, TBD can be considered a suitable metal-free catalyst alternative for the synthesis of polyesters which are used in compostable packaging or for biomedical applications. 18 The reactions will be performed in an eco-friendly, solvent-free approach. Relevant factors in this comparison study will be the amount of sorbitol implemented into the final polyester, the amount of catalyst used, the reaction time necessary to reach the required number-average molecular weight for coating applications and the properties of the final polyester.…”
Section: Introductionmentioning
confidence: 99%